2002
DOI: 10.1002/jsfa.1231
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll disappearance and chlorophyllase activity during ripening of Capsicum annuum L fruits

Abstract: The disappearance of chlorophyll pigments and involvement of chlorophyllase during fruit ripening of seven Capsicum annuum cultivars (Delfin, Mana, Belrubi, NuMex, Agridulce, Bola and Negral) have been studied. Chlorophyll pigments decreased and eventually disappeared from the red cultivars during ripening. In contrast, the green cultivar Negral, a chlorophyll-retaining variety, showed reduced disappearance of chlorophyll pigments, and the fully ripe fruits retained chlorophylls. Chlorophyllase activity follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The opposite is in the fruit, because during fruit ripening, the content of chlorophylls degraded and converted to colorless metabolites, and then carotenoids become perceptible, because that the low content of chlorophylls is indicative of fruit ripeness. Vegetables are a good source of chlorophylls compared to fruits [31,33,42]. Furthermore, A. ursinum leaves should be collected before the flowering period, i.e., from March to May.…”
Section: Chlorophyllsmentioning
confidence: 99%
“…The opposite is in the fruit, because during fruit ripening, the content of chlorophylls degraded and converted to colorless metabolites, and then carotenoids become perceptible, because that the low content of chlorophylls is indicative of fruit ripeness. Vegetables are a good source of chlorophylls compared to fruits [31,33,42]. Furthermore, A. ursinum leaves should be collected before the flowering period, i.e., from March to May.…”
Section: Chlorophyllsmentioning
confidence: 99%
“…The H * value of the skin is a typical indicator of changes in color during pepper ripening,11 which is associated with enzymatic degradation of the chlorophyll and an increase in carotenoid biosynthesis, reflecting the transformation of chloroplasts into chromoplasts 8, 9. Therefore, skin H * was able to discriminate among different maturity stages and consequently was a good maturity index.…”
Section: Resultsmentioning
confidence: 99%
“…Several harvest indices have been proposed to characterize the ripening process, particularly in the case of non‐climacteric pepper, such as changes in skin color and fruit firmness, the total soluble solids content or titratable acidity 6. A more sophisticated method is to measure the xanthophyll esterification that accompanies carotenoid over‐accumulation8 or the degradation of chlorophylls 9. An acceptable flavor (including volatile profiles) and the maintenance of fruit structural integrity during the post‐harvest handling phase to avoid decay are desirable 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Aljuburi et al (1979) found that in greening oranges, Chlase and chlorophyll content increased at the same time. However, in Capsicum annuum L. fruit, Chlase activity and chlorophyll losses were not correlated (Hornero-Méndez and Mínguez-Mosquera, 2002). Studies with different olive cultivars growing in the south of Spain have shown that during the fruit growth stage, which coincides with chlorophyll synthesis, Chlase was present in the cultivars studied.…”
mentioning
confidence: 84%